The Health Implications of Perceived Anti-Muslim Discrimination Among South Asian Muslim Americans - Naheed Ahmed, PhD; Nadia S. Islam, PhD (Elsevier, 2023)
Introduction: Anti-Muslim discrimination in the U.S. has increased exponentially since 2001, but the impact of anti-Muslim discrimination has yet to be fully examined because of limited data available on this topic and population. The objectives of this study were to (1) examine the association between perceived anti-Muslim discrimination and health risk behaviors, with depressive symptoms as a potential mediator, among South Asian Muslim Americans and (2) examine the association between other forms of perceived discrimination and health risk behaviors, with depressive symptoms as a potential mediator, among South Asian Muslim Americans. Methods: Data were collected using an online survey, which was disseminated on subscriber e-mail lists for organizations that serve South Asian or Muslim communities. Participants were asked about perceived discrimination, depressive symptoms, diet, physical activity, tobacco use, and alcohol consumption. Data were analyzed using structural equation modeling in Mplus 8. Results: Societal anti-Muslim discrimination had a positive association with depressive symptoms (0.19, p<0.05), as did interpersonal anti-Muslim discrimination (0.20, p<0.05) and other forms of discrimination (0.22, p<0.05). None of the discrimination scales were associated with dietary patterns, tobacco use, or alcohol consumption. Conclusions: Study results demonstrated a link between discrimination and depressive symptoms. Further research is needed to examine associations with other adverse health outcomes and potential buffers against discrimination.